Various Aspects for Data Migration in Cloud Computing and Related Reviewa - Kaur, Parneet; Majithia, Sachin (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing systems are deployed,which represents a real shift in the way. Cloud computing systems, are having the massive scale popularization of the Internet and was able to develop some large service companies. Cloud computing is a pay-as- you-go, infinitely scalable, ubiquitous computing systems, with the possible utility makes long-held dream. With cloud computing, you too can start small and grow very fast. That`s why itï¿½s built on. technology is evolutionary, even though cloud computing is revolutionary. The resources are limitless virtual and physical systems on which the software runs out of the details of the user that is different from that perception. In the current paper we are going to present problems of data migrations in cloud computing and also present different reviews of cloud computing.